The Role of Hospital Administration in Supporting MSMEs Through Corporate Social Responsibility (CSR) Health Programs - Miftahul Jannah; Juli Evianna Br Purba (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the role of hospital administration in supporting the development of MSMEs through the implementation of CSR programs in the healthcare sector. Using a quantitative approach, this study involved 10 hospitals and 50 partner MSMEs in North Sumatra. The results showed that the higher the intensity of CSR support provided by hospitals, the higher the increase in turnover and satisfaction of MSME partners. A well-structured CSR program can encourage the sustainability of MSME businesses while strengthening the hospital's positive image in the community. More than just social responsibility, CSR in this context serves as a collaborative bridge between healthcare institutions and small business owners. Hospital administration plays a crucial role in designing, managing, and evaluating the program's success, so that CSR implementation becomes not only a routine obligation but also a sustainable local economic empowerment strategy. Through the data and analysis conducted, this study demonstrates that a systematic and measurable approach from hospitals can produce tangible social and economic impacts for MSME partners. Thus, the role of hospital administration is not only functioning behind the scenes of medical services, but also as a social driver that contributes to the economic growth of the surrounding community through real and sustainable MSME empowerment.